Analysis of the thermal performance and convection effects in an aluminum holding furnace using CFD. (5th February 2015) - Carmona, Mauricio; Cortés, Cristóbal
Abstract: Detailed numerical simulations are used to estimate the thermal behavior of an aluminum holding furnace heated by a system of electrical resistances. Estimated temperatures are compared with experimental measurements taken in a real prototype. As a first approach, the symmetry of the geometry is used to reduce the computational resources and only a quarter of domain is initially simulated. Nevertheless the predicted velocities for the flow in the molten load suggest that the patterns induced by the convection effects have a three dimensional behavior. For this reason a new simulation with the full domain is carried out. Both simulations predict almost the same temperatures and energy distributions with different patterns of flow in the molten load. Chaotic behavior is predicted by the full domain approach for the movement of the aluminum bath, which corresponds to problems of natural convention with small differences in temperature and density due to the high thermal conductivity of the material. Although the effects on the thermal performance are very small or even undistinguishable, variations in the movement of the molten load may affect other aspects, such as for instance, the metallurgical properties of the final products. Highlights: A CFD analysis of a holding furnace of aluminum has been accomplished. Models used include all relevant phenomena to estimate the furnace performance. Two different geometries have been simulated: full and quarter of the furnace. The estimated flow behaviors by the two calculations differ considerably. Estimations of the thermal performance are very similar for both calculations.